O parque da cidade: requalificação urbana para o rio tubarão, SC – análises e oportunidades - Pereira, Helen Costa (2017)
From the perspective of sustainable development in contemporary cities rescue the desirable city water dimension the research focuses on the rescue possibilities of the Tubarão River, Santa Catarina, at the dimension of the city urbanity: a large area of public environmental potential who lost his connection to the city, even though being the element responsible for its formation and historical development. The redevelopment of the river waterfront, allowing its appropriation for socializing and recreation, enables the recovery of the importance of the river to the city. The work is organized in three parts-chapters that complement and integrate itselfes: The Problem; The Demand; The Desire. The Problem brings the analysis of Tubarão River in the urban evolution of the city and presents its current context. The demand refers to the typical erratic approaches of our cities in the 20th century, essentially, in which our urban rivers were forgotten and renegades, and the current rehabilitation trends, bringing some successful cases of recovery of the relationship between city and water, international and brazilian, and possible approaches to questioning the Tubarão case. The Desire shows the current and future possibilities of rehabilitation of the river shores of Tubarão River and its City Park. Studies of reference projects set parameters in order to justify the implementation of a linear park along the river. It also seeks that this research will serve as a basis for the creation of spaces that foster the humanization of the city and urban interaction with the river.